X-ray magnetic circular dichroism in d and f ferromagnetic materials: recent theoretical progress. Part I (Review Article): - Antonov, V.N.; Shpak, A.P.; Yaresko, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The current status of theoretical understanding of the x-ray magnetic circular dichroism (XMCD) of 3dcompounds is reviewed. Energy band theory based upon the local spin-density approximation (LSDA) describesthe XMCD spectra of transition metal compounds reasonably well. Examples which we examine in detail are XPt3 compounds (with X = V, Cr, Mn, Fe, Co, and Ni) in the AuCu3 structure, Heusler compoundsCo2MnGe, Co2NbSn, and compounds with noncollinear magnetic structure IrMnAl and Mn3ZnC. Recentlyachieved improvements for describing the electronic and magnetic structures of 3d compounds are discussed.